Exploring the Role of Social Media in Enhancing Micro and Small Business Performance (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The effects of social media and socioeconomic activities on micro and small businesses (MSEs) in India were investigated in this research. A structured questionnaire was used to gather primary data from 25 respondents as part of a quantitative research methodology. The results showed that social media has a major impact on customer engagement, sales performance, connection development, and buying behavior. Furthermore, it was discovered that socioeconomic factors as well as general economic circumstances (like monetary policy, fiscal policy, exchange rate etc.) have an impact on firm sustainability and profitability. According to the findings, favorable socioeconomic activities benefited financial performance, while social media platforms increased market awareness and facilitated well-informed decision-making. Overall, the research made clear how crucial it is to combine social media tactics with favorable economic circumstances in order to boost the expansion and competitiveness of micro and small businesses in India.